Spinal cord injury/dysfunction and medication management: a qualitative study exploring the experiences of community-dwelling adults in Ontario, Canada. Issue 1 (11th January 2022) - Cadel, Lauren; Hitzig, Sander L.; Packer, Tanya L.; Patel, Tejal; Lofters, Aisha K.; Thompson, Alison; Guilcher, Sara J. T.
Abstract: Purpose: To explore the attitudes, beliefs and experiences pertaining to the management of prescribed and unprescribed medications among community-dwelling adults with spinal cord injury/dysfunction (SCI/D) in Ontario, Canada. Materials and Methods: In-depth semi-structured interviews were conducted by telephone. Each interview was audio-recorded, transcribed verbatim and analyzed using inductive thematic analysis. Results: Of the 19 participants, 11 were male and 8 were female, with an age range from 36 to 76 years; 14 participants had traumatic SCI and 5 had non-traumatic spinal cord dysfunction. All but three participants were taking five or more medications, including prescription medications, over-the-counter medications and natural health products. The three main themes identified were: disruptive nature of medications, fear of negative outcomes and self-management: playing a critical role. Conclusions: Medication management is a complex, multifaceted and non-linear process. Persons with SCI/D described experiences with medication-taking that are not well understood by current medication management frameworks. Thus, it is essential to broaden our lens and situate persons with SCI/D medication-taking experiences within self-management frameworks to allow for a more comprehensive and reflective understanding of their experiences. Based on the findings from this study, recommendations for future research, practice and policy have been suggested. IMPLICATIONS FOR REHABILITATION: Persons with spinal cord injury/dysfunction identified numerous challenges and concerns with medication use post-injury. Educational medication management programs should be implemented post-discharge to improve the state of knowledge around medications (indication, side effects, strategies for taking medications) and how to optimize medication management. In order to optimize experiences and outcomes, there is a need for explicit and ongoing discussions around medication management between persons with spinal cord injury/dysfunction and their healthcare providers.